Calvins Sozialethik und der Kapitalismus - Eßer, Hans Helmut (Hervormde teologiese studies, 1992)
Calvin’s social ethics and the origin of modem Capitalism This paper starts off by introducing the prejudices against the mentioned theme and its continuing effects, and stresses in the conclusion that the so-called Max Weber thesis was corrected by Weber himself. He explained its validity more in terms of seventeenth-century Puritanism than for its direct connection to the social doctrine of Calvin. The second heading reports the discussion and refutation of the Max Weber thesis in sociological, historical and theological literature. Calvin’s work on social-ethics is also honoured. The concluding ten theses sum up the importance of Calvin’s fundamental social-ethics for the solution of Geneva’s economic problems.